(De)constructions of Discourse in Group Analytic Perspectives of Homosexuality. (September 2016) - Anderson, Daniel
Group analysis as a discourse of knowledge has much to offer how we construct homosexuality. Yet despite this rich background, group analysis has been slow to construct a clear theory of psychosexuality, and specifically homosexuality. The aim of this article therefore is to consolidate and expand current conceptions of sexuality, through an exploration of homosexuality within group analytic theory using ideas such as discourse analysis, desire, jouissance, the Other and the role of language in the matrix of the group. The article proposes a number of urgent research questions for group analysts around experiences of differing sexualities in a therapeutic group.